PENGARUH KEMUDAHAN, KEMANFAATAN DAN KEAMANAN TERHADAP PREFERENSI KONSUMEN DALAM MENGGUNAKAN QRIS SEBAGAI SISTEM PEMBAYARAN NON TUNAI - Amelita Ika Sari; Eka Sri Wahyuni; Khairiah Elwardah (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the effect of ease of use, usefulness, and security on consumer preferences in using QRIS as a non-cash payment system. The research was conducted with a quantitative method, using a survey approach to students of the Sharia Economics Study Program, Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu. The research sample was selected using purposive sampling technique based on the criteria: active students who have used QRIS in transactions. Data was collected through an online questionnaire, with a total of 75 respondents. The results showed that partially, Ease of use (X1) and security (X3) have a significant influence on consumer preferences, while usefulness (X2) has no significant effect. Simultaneously, these three variables have a significant influence on consumer preference in using QRIS as a non-cash payment system.